The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/14017431.2016.1219044
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences and bleeding complications after PCI on first and second generation DES

Abstract: Despite higher risk profile, women treated with DES have similar outcomes as males in 1-year follow-up. However there is, an increased risk of in-hospital bleedings in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“… 36 Wanha et al also found that although the 1-year bleeding risk between females and males was similar after PCI therapy, females experienced a higher risk of in-hospital bleeding events. 37 Extending prior reports, the current study was also focused on elucidating the factors associated with the gender-disparities in bleeding events. As presented in Table 4 , ageing, diabetes mellitus and glycoprotein IIb/IIIa inhibitor use at peri-PCI period were associated with the gender-disparities in the composite bleeding events.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Wanha et al also found that although the 1-year bleeding risk between females and males was similar after PCI therapy, females experienced a higher risk of in-hospital bleeding events. 37 Extending prior reports, the current study was also focused on elucidating the factors associated with the gender-disparities in bleeding events. As presented in Table 4 , ageing, diabetes mellitus and glycoprotein IIb/IIIa inhibitor use at peri-PCI period were associated with the gender-disparities in the composite bleeding events.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the undeniable development of stent technology and the undisputed revolution linked with the introduction to the clinical practice of second-generation DES 25 still, the diabetes population seems to have a faint advantage from this novel technology 26,27 Several conceptional improvements in stent design and modality had been postulated and introduced to clinical practice to overcome these limitations. 28,29 Especially high expectations had been associated with bioresorbable materials [30][31][32] -two different concepts have been proposed to use the advantage of these novel materials.…”
Section: Discussionmentioning
confidence: 99%
“…28 Interestingly, the distribution of ARC-HBR criteria between females and males in our study was also different, which essentially reflects the sex-related dissimilarities in the burden of clinical comorbidities. 29 HBR females had a higher prevalence of CKD and moderate/severe anemia, 2 conditions that often occur concomitantly. By contrast, males were more frequently discharged on oral anticoagulant therapy.…”
Section: Discussionmentioning
confidence: 99%